DISTINGSING BID’AH DAN BUDAYA LOKAL DALAM PERSPEKTIF AL-QUR’AN DAN AL-SUNNAH - Sholeh, Moh. Jufriyadi; Yaqin, Muhammad Nurul; Rafiqi, Iqbal (Reflektika, 2025)
This journal article discusses the distinction between bid'ah (innovation) and local culture from the perspective of the Qur'an and Sunnah. This study was motivated by the interaction between Islam and various local cultures, which often raises questions about their compatibility with Islamic teachings, where there are concerns that local traditions may obscure the purity of the teachings. The method used is qualitative with a thematic (maudhu'i) analysis approach to verses of the Qur'an and Hadith, as well as a literature study of the views of scholars. This study finds that bid'ah, which is essentially an innovation in worship that has no shar'i basis, is firmly rejected based on the principle of the perfection of Islam. Meanwhile, local culture ('urf) can be accommodated as long as it does not conflict with the principles of tawhid, sharia values, and qath'i arguments, and contains benefits. The distinction between bid'ah and tradition is not just a matter of terminology, but concerns a way of religious thinking that determines whether the ummah will be inclusive or exclusive towards social reality. By examining the arguments from the Qur'an and Hadith and understanding maq??id al-syar?‘ah, it appears that cultural innovations can be accepted in Islam if they fulfill the conditions of maslahat and do not violate sharia.